Karakteristik Ibu Hamil Dengan Ketuban Pecah Dini Di RS. Setio Husodo - Wulandary, Herviza; Tambunan , Lili Yuliana (Cattleya Darmaya Fortuna, 2022)
Premature rupture of membranes is the rupture of the amniotic membranes before the birth process occurs which can occur at term or short term of gestation. Premature rupture of membranes is one of the causes of maternal and neonatal infections, premature labor, hypoxia, fetal deformity, increased incidence of CS, or failure of normal delivery. This study aims to find out the characteristics of pregnant women with premature rupture of membranes based on age, parity, and occupation, at Setio Husodo Kisaran Hospital in 2017. From the initial survey, researchers obtained data from the medical records of Setio Husodo Kisaran Hospital in 2017, it was found that ruptured membranes early as many as 99 mothers.This research is descriptive, using secondary data which can be recorded at Setio Husodo Kisaran Hospital in 2017